FINITE ELEMENT ANALYSIS OF SEISMIC CONCRETE STRUCTURES IN VIEW OF CREEP CORROSION OF CONCRETE AND FIXTURES - , А. В. (Municipal economy of cities. Series: «Economy science», 2013)
Corrosion of rebars is the key reason for time-dependent quality degrading of reinforced concrete structures. This problem is important for structures in seismic sensitive zones because it leads to deviations of the structure rigidity characteristics and may increase seismic inertia forces at simultaneous reduction of bearing capability in certain elements or at dangerous raise of stresses. This study proposes a clarified procedure to solve plane elastic problem for reinforced concrete. It assumes an application of new approximation for non-linear concrete strain diagram, development of a detailed finite element model for reproduction of effect generated under concrete/rebar bond forces, and also simultaneous record of influence of time-dependent factors (concrete creep and rebar corrosion on structural strained and stressed state).